Factores de riesgos, físicos, químicos, biológicos y ergonómicos a los que están expuestos el personal de enfermería del Hospital Vicente Rodríguez Witt de la ciudad de Loja - Riofrío Arboleda, Jehny Maricela (2015)
In this research factors occupational risks to which they are exposed professional nursing staff of Vicente Rodriguez Witt Hospital of the City of Loja ware determined, it was worked with an investigation descriptive and a quantitative approach, involving 30 nurses The results were represented in graphs in terms of its physical risks exposure level is medium, with respect to dry heat and noise; chemical risks, handling of cytostatics in a higher level of exposure; biological risks in a medium and high exposure to body fluids; the ergonomic risks in a higher level of exposure to prolonged standing. Finally the prevention of occupational risks is to reach the safety of services and ensure the health of workers, making necessary the continuous improvement of surveillance and control that are conducted from the Labour Inspectorate and Social Security in order to improve the tools for successful implementation of a genuine culture of risk prevention in health services. The risk is that working conditions that is likely to cause harm to health. The protection of workers against occupational risks requires an immediate and continuing institutional performance as the circumstances and with this alteration, complete with information and training of workers, aimed at a better understanding of both the true scope the risks from work as security measures. Keywords: staff nurse, occupational risk factors, physical, chemical, biological and ergonomic